Pengabdian Masyarakat melalui Kegiatan Pemanfaatan Pojok Baca untuk Meningkatkan Pengetahuan Literasi Membaca Anak melalui Kegiatan Membaca Desa Jenggalu Dusun III Mekar Sari - Agustya Erawati; Suci Dwi Putri; Anggita Novitasari; Bayu Lailatul Hasanah; Sinar Komalasari; Saadah Mardliyati (Lembaga Pengembangan Kinerja Dosen, 2024)
The activity of placing a Reading Corner as an effort to support the increase in community interest in reading in Jenggalu Village, Dusun III Mekar Sari is a community service activity motivated by a joint effort to increase literacy and interest in reading among the village community because in Jenggalu Village, Dusun III Mekar Sari does not provide a reading corner. This program aims to improve the literacy skills of the community with the support of a reading corner as well as being able to bring reading materials closer to the community while in Jenggalu Village Hamlet III Mekar Sari. The implementation methods used in community service include discussion methods, promotion and placement of reading corners in Jenggalu Village Hamlet III Mekar Sari. This activity involved village officials in the discussion and promotion process as well as the community so that on the first day after the initial laying of the reading corner the number of visitors was quite a lot, namely 16 people and the visitors' responses were very positive and felt lucky because in Jenggalu Village Dusun III Mekar Sari there was already a reading corner that not only benefited the village but also the people of Jenggalu Village Dusun III Mekar Sari in increasing reading literacy in Jenggalu Village Dusun III Mekar Sari